The Integration of Agrarian-Maritime Economy in the Diplomacy of the Demak Sultanate in the 16th Century - Hilmi, Zonni Bahauddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines how the Sultanate of Demak established and utilised the 16th-century international trade networks of Southeast Asia as a basis for consolidating its political power. The main research question is: how did the political-economic structure of Demak’s trade emerge, and how did the integration of agrarian and maritime economies play a role in shaping and consolidating the political power of the Demak Sultanate within the 16th-century Southeast Asian trade network? Unlike previous studies that emphasised religious and dynastic aspects, this research employs a political-economic approach to position trade as a structural variable in state formation. The method employed is a historical approach through the stages of heuristics, source criticism, interpretation, and historiography, utilising local chronicles, Portuguese chronicles, and Southeast Asian maritime studies. The research findings indicate that Demak functioned as a port-polity that controlled port strategies, managed the distribution of key commodities such as rice and teak wood, and integrated coastal elites into the regional trade network. Through control over commodity flows and maritime mobility, Demak not only participated in international networks but actively built and expanded them as a basis for legitimising and extending its power. These findings reinforce the argument that trade was the foundation for the formation of the early Islamic state in Java.